2021
DOI: 10.1371/journal.pone.0247295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, reasons, and determinants of dietary supplements use among undergraduate female students of health and non-health colleges in a Saudi public university

Abstract: Purpose The aim of this study was to gather data from female students studying in both health and non-health colleges at Imam Abdulrahman Bin Faisal University and report the prevalence, reasons, and determinants of dietary supplements use. Methods A month-long cross-sectional study was conducted in health and non-health colleges affiliated to Imam Abdulrahman Bin Faisal University in Dammam, Saudi Arabia. Convenient sampling was employed, and the data was gathered through an online survey using the English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…These points also detected by several previous studies [17,7,21,22]. The most prevalent reasons for DS consumption were to combat nutritional deficiencies (69%) and to boost immunity (48%) as which is also match with previous studies findings [7,23,24]. More than half of the individuals (54.4 percent) experienced at least one adverse impact when using DS during a specific timeframe; this result contradicts several published studies that reported the adverse effects that developed concurrently while using DS were low and sometimes infrequent [25].…”
Section: Discussionsupporting
confidence: 90%
“…These points also detected by several previous studies [17,7,21,22]. The most prevalent reasons for DS consumption were to combat nutritional deficiencies (69%) and to boost immunity (48%) as which is also match with previous studies findings [7,23,24]. More than half of the individuals (54.4 percent) experienced at least one adverse impact when using DS during a specific timeframe; this result contradicts several published studies that reported the adverse effects that developed concurrently while using DS were low and sometimes infrequent [25].…”
Section: Discussionsupporting
confidence: 90%
“…More emphasis should be placed on doctor’s or pharmacist’s opinion when choosing dietary supplements or over-the-counter medications. In the presented study, general practitioners or pharmacists were the sources of recommendation for only 16% of persons taking DS or OTC drugs for stress, anxiety, depression, or sleeping problems, which is much less than in some other studies [ 39 ].…”
Section: Discussionmentioning
confidence: 79%
“…This is difficult to compare with other studies because many of them focus on the general use of dietary supplements rather than specifically on supplements for stress, anxiety, depression, or sleeping problems; but in general, the trend is that women use DS more often [ 37 , 38 ]. Among the many reasons for taking the DS or OTC drugs reported by the students or young adults are relief of fatigue, focus enhancement [ 10 ], stress management, mental focus, concentration, improving the duration and quality of sleep [ 6 ], or memory enhancement [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 Rural living differs from urban living in many ways that could affect dietary supplement consumption and related consequences, besides other demographic factors. 20 Several epidemiological studies also opine that demographic factors may influence supplement consumption. 19,20 Old age, female gender, degree of education, affordability and employment status are a few prominent demographic characteristics linked to increasing dietary supplement usage.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several epidemiological studies also opine that demographic factors may influence supplement consumption. 19,20 Old age, female gender, degree of education, affordability and employment status are a few prominent demographic characteristics linked to increasing dietary supplement usage. 21 The current study reported that overall, 59.27 % of nutraceutical users belonged to urban dwellings.…”
Section: Discussionmentioning
confidence: 99%